Identification of Nematodes Associated with Citrus Trees in Dalanj Area, Sudan - Eisa M. Ahmed; Nigood M. Omer; Taisser A. Almaleeh (Research Highlights in Agricultural Sciences Vol. 4, 2022)
The specific objectives of this study were to survey and identify the types of nematodes associated with citrus trees in the Dalanj area; to determine infection level, and to examine some botanical extracts in controlling (Xiphinema basiri) in citrus. The Bearman funnel technique was used to extract the juveniles from the soil. Nematode identification is primarily based on the nematode’s body measurements. Water extracts were used to make botanical extracts. After 24, 48, and 72 hours, the mortality rates of juveniles were recorded. The species was identified as Xiphinema basiri based on morphological characteristics of the nematode. Juvenile mortality rates increased as concentration and exposure time increased.The extracts from the bark of Punica grantum, seeds of Moringa oleifera, and seeds of Croton zambesias, were found to be extremely toxic to juveniles of Xiphinema basiri (35.33, 30.33, and 26.33%), respectively, after 72 hrs, at a concentration of 10.000 ppm, compared to the average mortality rates of juveniles treated with Cassia senna leaves and Moringa olifera (21and 19.67%). At 100ppm, all botanical extracts had low mortality rates of 24.67-10% after 72 hours, with only the extract from the bark of Punica grantum showing mortality rates above 20% at all exposure times. The seed extracts all had higher nematicidal activity than the leaf extracts.